Analysis of support system for a conveyance tunnel in the higher Himalayan zone: A case study on Upper Tamakoshi HEP, Nepal - Paudyal, Kalyan (Journal of Innovations in Engineering Education, 2021)
After excavation, insitu stress conditions are changed which lead deformation due to the stress concentration. For the stability in the excavated tunnel profile, appropriate support system is essential. To recommend the support system, site specific data are used from Higher Himalayan Region of Nepal. Study is focused on 3 m and 6 m size inverted D Shaped tunnel with three different overburden thickness. For the analysis of support system: Empirical method, Analytical method and Numerical Modeling are performed. Result obtained from the different approaches for three different overburden heights as well as for both size tunnels are compared and finally required support system is recommended. It was found significant change in deformations while increase in size of tunnel. Overburden thickness is also playing the vital role in this parameter but size effect is more prominent.